(untitled) (Journal of Educational Sciences, 2016)
Статья рассказывает об ожидаемых результатах в сфере подготовки педагогов к компетентному овладению информационно-коммуникационными технологиями в системе повышения квалификации. Тhe article is about expectation results in preparing teachers sphere, to take over information communication technology in rise qualification system.